ANALISA UNJUK KERJA MOTOR BAKAR BERBAHAN BAKAR BIOGAS TERMURNIKAN BERBASIS ABSORBER Fe2O3 - Sutanto, Rudy; Alit, Ida Bagus; Nurchayati, N. (Dinamika Teknik Mesin: Jurnal Keilmuan dan Terapan Teknik Mesin, 2014)
Long-term aim of this research is to obtain a biogas what the renewable natural gas quality and can be used to fuel an electric generator to support the availability of electricity in the region of small islands. Specific targets to be achieved is to determine whether the binding of H2S in biogas can raise engine peformance of the machine, information technology and the active materials so comprehensive to absorb hydrogen sulfide gas as materials of the textbook writing and articles for national journals. This research will be conducted a biogas testing in the engine performance, seen from the engine rotation (1500, 2500, 3500 and 4500 rpm) of the electric power generated and subtlety spin machine (braking force, fuel consumption) in both the before purified biogas and biogas has been purified. Results of the research that has been conducted in both the before purified biogas and biogas has been purified on peformance engine that does not change significantly for the better performance of the engine torque, effective power and fuel consumption (biogas) to treat a wide variety. Effect of reduction of H2S contained in the biogas no significant effect on engine performance but are more inclined towards corrosive metal material. Keywords: biogas, performance, torque, effective power